Computational Fluid Dynamic Analysis of Different Velopharyngeal Closure Patterns. (February 2020) - Huang, Hanyao; Yin, Heng; Wang, Yang; Chen, Nan; Huang, Dantong; Luo, Xiangyou; Yin, Xing; Zheng, Qian; Shi, Bing; Li, Jingtao
Objective: Velopharyngeal (VP) closure has high impact on the quality of life, especially in patients with cleft palate. For better understanding the VP closure, it is important to understand the airflow dynamics of different closure patterns, including circular, coronal, sagittal, and circular with a Passavant's ridge. The purpose of this study was to demonstrate the airflow characteristics of different velopharyngeal closure patterns. Methods: Sixteen adults with no notable upper airway abnormality who needed multislice spiral computed tomography scans as part of their clinical care. Airways were reconstructed. A cylinder and a cuboid were used to replace the VP port in three models of VP port patterns. Flow simulations were carried using computational fluid dynamics. Airflow pressures in the VP orifice, oral cavity and nasal cavity, as well as airflow velocity through the velopharyngeal orifice, were calculated. Results: The airflow dynamics at the velopharynx were different among different velopharyngeal patterns as the area of the velopharyngeal port increased from 0 to 25 mm 2 . The orifice areas of different closure conditions in four velopharyngeal closure patterns were significantly different. The maximal orifice area for adequate velopharyngeal closure was 7.57 mm 2 in the coronal pattern and 6.21 mm 2 in the sagittal pattern. Conclusions: Airflow dynamics of the velopharynx were correlated to the velopharyngeal closure patterns. Different closure patterns had different largest permitted orifice areas for getting the appropriate oral pressures for normal speech.